Guest Editorial - Dolly Samson (Laureate Education Inc, 2013)
It is an honor and a pleasure to have the December 2013 issue of Higher Learning Research Communications dedicate its issue to selected papers from the 4th International Conference on Teaching and Learning, held in Bangkok in November, 2013. The conference theme, Higher Learning in the ASEAN Context, highlights the emerging community of ten Southeast Asian nations and the upcoming launch of the ASEAN Economic Community (AEC) in 2015. The AEC will affect higher education systems in Southeast Asia in terms of harmonization of higher education and student mobility. This emerging regional demographic gives us a glimpse of the future of transnational education. The papers selected for this issue represent research both within and outside of ASEAN, all touching on aspects of transnational education. Jeannin reports on how diversity affects students' learning in an international classroom in Thailand. Billingham, Gragg, and Bentley (Australia) highlight technology integration as an internationalizing practice. Ling considers challenges and outcomes of bilingual teaching and learning at the graduate level in Vietnam, contributing to the postgraduate educational field, which has not been amply explored in this matter. Stetz and Bauman (US) ask us to rethink the efficacy of recording our lectures for online viewing. Hartfield (Australia), Beltram-Cruz (Philippines), and Cruz (Philippines) review new pedagogical paradigms utilizing technology. Al-Masum and Chowdhury report on problems and progress at Bangladesh Open University in bringing higher education to an underserved population. Throughout this issue, the authors bring a sense of internationality and the transnational transformation of higher education, along with the ubiquity of technology in the hands of the students and its impact on our teaching and learning styles. This issue of the HLRC Journal highlights some impacts that ASEAN and the AEC can and will have on higher education everywhere.